Early response of selected tree species to liberation thinning in a young secondary forest in Northeastern Costa Rica - Guariguata, Manuel R. (1999)
Short-term growth responses in individuals of four commercial tree species (Laetia procera, Simarouba amara, Tapirira guianensis, and Vochysia ferruginea) were evaluated one and two years after `liberation thinning' in a young (4.5-year-old), dense secondary forest stand located in an agricultural settlement in wet, Northeastern Costa Rica. Liberation thinning involved manual elimination (either by cutting or stem girdling) of the adjacent `ring' of competitors in order to release future crop trees (median diameter: 8 cm DBH), selected on the basis of stem and crown form. The application of liberation thinning significantly increased diameter growth of future crop trees with respect to unmanipulated counterparts. Young stands in the region may be attractive systems for simple silvicultural manipulations due to rapid growth responsiveness, facilitated by manageable tree size. Detailed observations on stand development and patterns of crown stratification in coexisting tree species in other dense secondary stands in the area seems warranted in order to refine silvicultural options aimed at increasing tree diameter growth.